Facial Growth in the Rhesus Monkey : a Longitudinal Cephalometric Study. - Schneiderman, Emet D. (Princeton : Princeton University Press, 2014)
For a wide spectrum of scientists from biomedical and dental researchers to primatologists and physical anthropologists, Emet Schneiderman offers the most accurate and up-to-date presentation of the normal growth of the lower facial skeleton in a primate species. His study is based on a sample of thirty-five captive rhesus monkeys, whose facial growth was traced over a ten-year period spanning from infancy to adulthood. The author identifies the relative contribution of various sites of growth, quantifies the relative roles of different types of development--such as appositional and condyla.
Frontmatter -- CONTENTS -- LIST OF FIGURES -- LIST OF STATISTICAL TABLES (APPENDIX C) -- ACKNOWLEDGMENTS -- 1. INTRODUCTION -- 2. MATERIALS AND METHODS -- 3. AGE ESTIMATION -- 4. RESULTS -- 5. DISCUSSION -- 6. CONCLUSIONS -- APPENDIXES -- REFERENCES -- AUTHOR INDEX -- SUBJECT INDEX
Print version record.
Cover; Contents.
JSTOR
Keywords: Rhesus monkey -- Growth; Face -- Growth; Cephalometry; Longitudinal method; Cephalometry; Longitudinal Studies; Macaque rhésus -- Croissance; Céphalométrie.; Méthode longitudinale; SCIENCE -- Life Sciences -- Biology; NATURE -- Animals -- Mammals; SCIENCE -- Life Sciences -- Zoology -- Mammals; Cephalometry; Face -- Growth; Longitudinal method